Educational Services Marketing - Muallief Umar; Hasyim Nawawi; Nuraini Latifah; Agus Eko Sujianto (EDUTEC : Journal of Education And Technology, 2021)
This research aims to expose the importance of Marketing in the world of education is indispensable, with the aim to introduce schools or Madrasahs for prospective new students with respect to the quality of the school. Competition in the world of education is very interesting, so special strategies are needed in educational marketing. Effective marketing of educational services will have good feedback about the school because the image of the school in the community will be better and the school will attract new students. The purpose of this research is to describe and analyze: (1) marketing of Educational services, (2) Implementation of Education Services Marketing. Evaluation. The approach used in this research is a qualitative approach with case study research design. The data collection techniques in this study use interviews, observations, and documentation studies. The data obtained is then analyzed by data condensation techniques, data presentation, and data verification. The results showed that: 1.Formulation of SDINU Pare in the marketing of educational institution services, with the form of making a superior program of Tahfidz activities. 2. Implementation or implementation of agency marketing at SDINU Pare begins with the implementation of Tahfidz's flagship program and registration using talent and interest channels. 3. The evaluation conducted by SDINU Pare is evaluated by institutional meetings where the implementation of the evaluation of marketing of educational institution services through Tahfidz's flagship program activities, acceptance of interest and talent pathways, as well as continuous marketing promotion. This is done to see the extent to which the effectiveness of marketing the services of educational institutions needs to be changed or revised. Follow-up will be done if there are deficiencies in terms of marketing the agency's services, and follow-up will be carried out for implementation in the following year.